Harmonization of Administrative-Criminal Sanctions for State Losses After Constitutional Court Decision No.66/PUU-XXIV/2026 - Risman Setiawan (Nusantara: Journal of Law and Islamic Law, 2026)
The harmonization of administrative and criminal sanctions in addressing state financial losses following Constitutional Court Decision No. 66/PUU-XXIV/2026. The primary issue involves overlapping authority between internal oversight bodies and law enforcement agencies, creating potential legal uncertainty for public officials. Using a quantitative, comparative research design, the study analyzes secondary data on state loss cases before and after the ruling through descriptive and inferential statistical methods. The findings indicate that applying actual loss parameters and clearly distinguishing between maladministration and criminal acts of corruption significantly improves legal certainty and enhances state asset recovery. Enhanced coordination between internal oversight bodies and law enforcement agencies increases the effectiveness of administrative compensation mechanisms. Overall, harmonizing sanctions based on the principle of ultimum remedium balances safeguarding official discretion and ensuring proportional enforcement of anti-corruption laws. The results provide guidance for law enforcement policies that prioritize asset recovery while preventing the undue criminalization of policy decisions.